Resource Allocation in a Cognitive Radio System with Imperfect Channel State Estimation - Tao Qin; Cyril Leung; Chunyan Miao; Zhiqi Shen (Journal of Electrical and Computer Engineering)
Cognitive radio (CR) is a promising concept for improving the utilization of scarce radio spectrum resources. Orthogonal frequency division multiplexing (OFDM) is regarded as a technology which is well matched for CR systems. It is shown that channel estimation errors can result in a severe performance degradation in a multiuser OFDM CR system. A simple back-off scheme is proposed, and simulation results are provided which show that the proposed scheme is very effective in mitigating the negative impact of channel estimation errors.